rchg.net
当前位置:首页 >> ArCsinx 178 >>

ArCsinx 178

解: 令t=arcsinx,则x=sint,dx=cost dt ∫(arcsinx)²dx =∫ t²·cost dt =t²·sint-∫ 2t·sint dt =t²·sint+∫ 2t·d(cost) =t²·sint+2tcost-∫ 2cost dt =t²·sint+2tcost-2sint+C =x·arcsin²x+2arcsinx·√(1-x...

解: 令arcsinx=u,则x=sinu ∫(arcsinx)²dx =∫u²d(sinu) =u²sinu-∫sinud(u²) =u²sinu-∫2usinudu =u²sinu+2∫ud(cosu) =u²sinu+2ucosu-2∫cosudu =u²sinu+2ucosu-2sinu +C =(arcsinx)²x+2√(1-x²...

∫(arcsinx)^2·dx =x(arcsinx)^2-∫x·2arcsinx/√(1-x²)·dx =x(arcsinx)^2+∫2arcsinx·d[√(1-x²)] =x(arcsinx)^2+2arcsinx·√(1-x²) -∫2√(1-x²)·1/√(1-x²)·dx =x(arcsinx)^2+2arcsinx·√(1-x²)-∫2dx =x(arcsinx)^2+2arc...

y=ln(arcsinx²) y'=(arcsinx²)'/arcsinx²=(x²)'/[arcsinx²√(1-x⁴)] =2x/[arcsinx²√(1-x⁴)]

∫arcsinx dx = xarcsinx - ∫x darcsinx = xarcsinx - ∫x/√(1 - x²) dx = xarcsinx + ∫1 /[2√(1 - x²)] d(1 - x²) = xarcsinx + √(1 - x²) + C

f(x)=(arcsinx)² f'(x)=2(arcsinx)/√(1-x²) f''(x)=2[√(1-x²)²+arcsinx·2x/2√(1-x²)]/√(1-x²)² =2[(1-x²)√(1-x²)+x·arcsinx]/[(1-x²)√(1-x²)] (1-x²)f''(x)-xf'(x) =2[(1-x²)...

求不定积分∫(arcsinx)/[x²√(1-x²)]dx解:令x=sinu,则u=arcsinx,dx=cosudu; 故原式=∫udu/sin²u=∫ucsc²du=-∫ud(cotu)=-ucotu+∫cotudu =-ucotu+∫d(sinu)/sinu=-ucotu+ln∣sinu∣+C =-(arcsinx)[(1/x)√(1-x²)]+ln∣x∣+C

求arcsinx-arcsiny=α的图像 解:arcsiny=arcsinx-α 故y=sin(arcsinx-α)=sin(arcsinx)cosα-cos(arcsinx)sinα =xcosα-[√(1-x²)]sinα xcosα-y=[√(1-x²)]sinα 平方去根号得x²cos²α-2xycosα+y²=(1-x²)sin²α 即有x...

将分子拆开。 原式 =∫x/√(1-x²)dx+∫arcsinx / √(1-x²)dx =-√(1-x²)+∫arcsinx d(arcsinx) =-√(1-x²)+1/2(arcsinx)²+C。

y=√(1-x²)*arcsinx,那么y'=[√(1-x²)]'*arcsinx+√(1-x²)*(arcsinx)'显然[√(1-x²)]'=-2x/2√(1-x²)=-x/√(1-x²)(arcsinx)'=1/√(1-x²)所以y'=-x/√(1-x²)*arcsinx+1

网站首页 | 网站地图
All rights reserved Powered by www.rchg.net
copyright ©right 2010-2021。
内容来自网络,如有侵犯请联系客服。zhit325@qq.com